2020
DOI: 10.3390/dj8040108
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Shear Bond Strength of Orthodontic Brackets after Enamel Conditioning with Acid Etching and Hydroabrasion

Abstract: The purpose of this study was to evaluate the shear bond strength and adhesive remnant index ARI) of orthodontic brackets following enamel conditioning with acid etching, hydroabrasion, and with both procedures. Thirty extracted human premolars were divided into three groups and received either acid etching, hydroabrasion or both procedures. Orthodontic brackets were bonded with composite resin. Shear bond strength was tested with a tensile machine, then the teeth were observed under a stereomicroscope to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Our research findings indicated that the enamel surface in both the TC and SD groups was nearly returned to its pre-treatment condition following the polishing. The results gave a smooth surface and less time than other burs like SD spiral, which needs to change the spiral and consumes time [ 26 28 ]. However, the surface roughness decreased significantly in the DB group, but the surface still had a slightly rough surface with shallow grooves.…”
Section: Discussionmentioning
confidence: 99%
“…Our research findings indicated that the enamel surface in both the TC and SD groups was nearly returned to its pre-treatment condition following the polishing. The results gave a smooth surface and less time than other burs like SD spiral, which needs to change the spiral and consumes time [ 26 28 ]. However, the surface roughness decreased significantly in the DB group, but the surface still had a slightly rough surface with shallow grooves.…”
Section: Discussionmentioning
confidence: 99%
“…If the acid-etching time of tooth enamel had been shortened, it would have positive effects on lower tooth demineralization but not by reducing the bond strength of the two adherents. Obtaining a quality ultrastructural morphology of human teeth enamel will give better opportunities for penetration of adhesive materials (28,29) because the strength of the shear bond between enamel and bracket bases is only one of the components that affects the final outcome in clinical conditions. In addition, the bonding area size (contact of the brackets' bases with the demineralized zone) is also a significant factor in obtaining an optimal bond strength between the two adherents.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to prosthetic restorations brackets need to bond to the teeth only for a limited time period of approximately 2 years 35 , but on the other hand there must be a reliable adhesion throughout the whole multibracket treatment to avoid prolonged treatment times 36 and undesired tooth movement if teeth are not fixed to the wire. Therefore, including aging regimens into orthodontic SBS testing seems to be of major importance, although this aspect still not considered in many orthodontic SBS studies 1 , 29 , 37 , 38 . Despite of thermal cycling, SBS was tested after 90 days of wet storage at 37 °C.…”
Section: Discussionmentioning
confidence: 99%
“…For orthodontic treatment with fixed appliances brackets are usually bonded to the enamel surface, using the etch and rinse technique and phosphoric acid 1 . According to the literature shear bond strength (SBS) values between enamel and bracket of 5–10 MPa are recommended 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%